Rapid Automation 2019
DOI: 10.4018/978-1-5225-8060-7.ch066
|View full text |Cite
|
Sign up to set email alerts
|

Critical Thinking and Digital Technologies

Abstract: The aim of this study is to identify the new trends on technology use in developing critical thinking skills. By this purpose, the researches published between 2008-2014 in Science Direct database were examined by using content analysis. Also study was completed in three main parts. The first part consists of the conceptual framework about, technology use in education, critical thinking, the effect of technology on critical thinking and new technologies used to develop critical thinking skills. In the second p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…) andDichek et al (2021), who argued that students who develop critical thinking have better learning outcomes. They are consistent with the results ofGiraldo-García et al (2015),Gökçearslan et al (2019),Lychuk et al (2021),Nozhovnik and Shykhnenko (2020),Schindler et al (2017), who found that the use of technology increases students' motivation, provides individualization of learning, improves their time management skills and overall learning satisfaction. The results of the study deepen the provisions introduced byDehghani et al (2011), Lin et al (…”
supporting
confidence: 92%
See 1 more Smart Citation
“…) andDichek et al (2021), who argued that students who develop critical thinking have better learning outcomes. They are consistent with the results ofGiraldo-García et al (2015),Gökçearslan et al (2019),Lychuk et al (2021),Nozhovnik and Shykhnenko (2020),Schindler et al (2017), who found that the use of technology increases students' motivation, provides individualization of learning, improves their time management skills and overall learning satisfaction. The results of the study deepen the provisions introduced byDehghani et al (2011), Lin et al (…”
supporting
confidence: 92%
“…Technologies were found to positively affect students' critical thinking, academic performance and career development, as they eliminate the dominance of explanatory-illustrative learning by substituting student-task-outcome-centred approaches to learning (Lupak et al, 2020). The technology-driven learning environment also provides individualisation of learning and increases student learning motivation (Giraldo-García et al, 2015;Gökçearslan et al, 2019;Lychuk et al, 2021;Nozhovnik & Shykhnenko, 2020;Schindler et al, 2017). Lychuk et al (2021) found that the above environment could be also organised as inquiry-based and learner-centred.…”
Section: Justification Of Procedures Presentation Of Arguments Self-r...mentioning
confidence: 99%
“…Technology tends to change the way we think. In order to survive the modern world, learners need life-long learning skills, to widen knowledge, adapt to changes, and successfully manage and produce information (Gökçearslan et al 2019). Efficient use of technology in a learning environment improves learners' study skills and ability to implement real-life situations and gain critical and problem-solving thinking skills.…”
Section: Digital Learning Don't Bother Teaching Students Give Them Tools To Lead To New Ways Of Thinking (Devisakti Annamali)mentioning
confidence: 99%
“…Innovations that take advantage of environmental issues in the learning process are theoretically able to form individuals who can think critically, creatively, and innovatively. One of the impacts of students learning with community technology science is that students can identify problems and be more creative in finding solutions to solve them (Gökçearslan et al, 2019). Students who have problem solving skills can apply the knowledge they have in the context of the problems they face.…”
Section: Problem Solving In Science and Technology Societymentioning
confidence: 99%